Compensatory mechanism of attention-deficit/hyperactivity disorder recovery in resting state alpha rhythms - Han, Chuanliang; Wang, Tian; Wu, Yujie; Li, Hui; Wang, Encong; Zhao, Xixi; Cao, Qingjiu; Qian, Qiujin; Wang, Yufeng; Dou, Fei; Liu, Jian K.; Sun, Li; et al. (Frontiers in Computational Neuroscience, 2022)
Alpha rhythms in the human electroencephalogram (EEG), oscillating at 8-13Hz, are located in parieto-occipital cortex and are strongest when awake people close their eyes. It has been suggested that alpha rhythms were related to attention-related functions and mental disorders (e.g. Attention-deficit/hyperactivity disorder (ADHD)). However, many studies have shown inconsistent results on difference of alpha oscillation between ADHD and control groups. Hence it is essential to verify this difference by a relatively larger sample size. Here a large dataset of EEG recording (128 channel EGI) from 87 healthy controls (HC) and 162 ADHD (141 persisters and 21 remitters) adults in resting state with their eyes closed was used to address this question and a three-gauss model (summation of baseline and alpha components) was conducted to fit the data. To our surprises, the power of alpha components was not significant different among three groups. Instead, the baseline power of remission and HC group in alpha band is significant stronger than that of persister groups. Our results suggest that the ADHD recovery may have compensatory mechanism and many abnormalities in EEG may be due to the influence of behavior rather than the difference of brain signals.